The Impact of Study Abroad on Kazakhstani Students’ Academic Expectations - Rakisheva, Aigul (Nazarbayev University Graduate School of Education, 2019)
This study aims to identify the impacts of studying abroad on Kazakhstani students’ academic expectations, for those who studied under the short-term Erasmus + academic mobility program as well as the experience of academic life at their home institutions after their return. Furthermore, the study employs a qualitative approach using the case study of a leading state university in cosmopolitan Kazakhstan as well as semi-structured interviews with ten university students. The findings reveal that students who participated in the program consider the Erasmus experience as a key element for academic performance and further professional growth. Additionally, the interviewees felt that their participation in the program helped them become more open, sociable, independent, and ready for new changes in life. Moreover, they expressed the belief that they had improved their critical thinking skills and had become more creative and active. Thus, according to study participants, educational institutions should actively provide the necessary information about the program to students as well as support returning students to create the appropriate conditions for the students’ academic activities. However, participants recognized concerns over language barriers, teaching, and bureaucratic problems at home institutions as well as a shock in adaptation after return. Consequently, it is necessary to conduct an in-depth study of the process of the participants’ re-entry in further research.
Keywords: short-term student mobility; internationalization; academic expectations; study abroad; Erasmus +